APLIKASI AUTO LEVEL SYSTEM DENGAN INTERLOCK PADA CONTINUITY BULK MATERIAL PEMBANGKIT LISTRIK BIOMASSA - Ahmad Aziz Mulyawan; Masayu Anisah; Iskandar Lutfi (JURNAL TELISKA, 2026)
Fuel supply continuity is a critical factor in maintaining stable boiler operation in biomass power plants. Common problems include empty fuel bins and material overflow caused by manual conveyor operation. This final project focuses on the application of an auto level system with interlock in the continuity bulk material system of a biomass power plant. The system utilizes photocell sensors to detect minimum and maximum fuel levels in the fuel bin, integrated with contactors and thermal overload relays (TOR) to control and protect the conveyor motor. The research methods include literature study, field observation, system design, simulation, and performance testing. The test results show that the system is capable of automatically controlling conveyor operation, preventing fuel shortages and overfilling, and improving operational safety and reliability. The implementation of this system also reduces operator workload and ensures stable fuel supply to the boiler.